CXCL17-mediated downregulation of type I collagen via MMP1 and miR-29 in skin fibroblasts possibly contributes to the fibrosis in systemic sclerosis. Issue 3 (December 2020) - Shimada, Shuichi; Makino, Katsunari; Jinnin, Masatoshi; Sawamura, Soichiro; Kawano, Yuya; Ide, Maho; Kajihara, Ikko; Makino, Takamitsu; Fukushima, Satoshi; Ihn, Hironobu
Highlights: CXCL17 reduced type I collagen expression via MMP1 and miR-29 in skin fibroblasts. CXCL17 levels in SSc skin were lower than those in healthy controls. CXCL17 attenuated the skin fibrosis induced by bleomycin in mice. Abstract: Background: Systemic sclerosis (SSc) is characterized by excessive deposition of collagen in the skin and internal organs. Recent studies have shown that chemokine (C-X-C motif) ligands (CXCLs) are involved in the pathogenesis of SSc. Objective: Our aim was to examine the anti-fibrotic potential of CXCL17, a newly discovered chemokine, in cultured skin fibroblasts and in a bleomycin-induced SSc mouse model. Moreover, we examined serum level of CXCL17 in patients with SSc. Methods: Type I collagen expression was evaluated in SSc skin and cultured fibroblasts treated with CXCL17 using immunoblotting and quantitative reverse transcription-PCR. Serum CXCL17 levels were determined using enzyme-linked immunosorbent assay in 63 patients with SSc and 17 healthy subjects. A bleomycin-induced SSc mouse model was used to evaluate the effect of CXCL17 on skin fibrosis. Results: CXCL17 reduced the expression of type I collagen in healthy control fibroblasts. CXCL17 also induced matrix metalloproteinase 1 (MMP1) and miR-29 expression in fibroblasts, indicating that CXCL17 regulates type I collagen expression in part via post-transcriptional mechanisms through MMP1 and miR-29. We found that local injection of CXCL17 attenuated bleomycin-induced skin fibrosis in mice. CXCL17 levels in SSc skin were lower than those in healthy controls, in contrast to the high serum CXCL17 levels in patients with SSc. The low expression of CXCL17 in SSc skin possibly affects type I collagen accumulation in this disease. Conclusion: Our data indicate that understanding CXCL17 signaling may lead to a better therapeutic approach for SSc.